FGF2 induces RANKL gene expression as well as IL1β regulated MHC class II in human bone marrow-derived mesenchymal progenitor stromal cells. Issue 1 (18th November 2013) - Bocelli-Tyndall, Chiara; Trella, Emanuele; Frachet, Audrey; Zajac, Paul; Pfaff, Dennis; Geurts, Jeroen; Heiler, Stefan; Barbero, Andrea; Mumme, Marcus; Resink, Therese J; Schaeren, Stefan; Spagnoli, Giulio C; et al.
Abstract : Objective: Human bone marrow mesenchymal stromal cells (hBM-MSC) are being applied in tissue regeneration and treatment of autoimmune diseases (AD). Their cellular and immunophenotype depend on isolation and culture conditions which may influence their therapeutic application and reflect their in vivo biological functions. We have further characterised the phenotype induced by fibroblast growth factor 2 (FGF2) on healthy donor hBM-MSC focusing on the osteoimmunological markers osteoprotegerin (OPG), receptor activator of nuclear factor kB (RANK), RANK ligand (RANKL) and HLA-DR and their regulation of expression by the inflammatory cytokines IL1β and IFNγ. Methods: RANK, RANKL, OPG and HLA-DR expression in hBM-MSC expanded under specific culture conditions, were measured by RT-PCR and flow cytometry. MAPKs induction by FGF2, IL1β and IFNγ in hBM-MSC was analysed by immunoblotting and RT-PCR. Results: In hBM-MSC, OPG expression is constitutive and FGF2 independent. RANKL expression depends on FGF2 and ERK1/2 activation. IL1β and IFNγ activate ERK1/2 but fail to induce RANKL. Only IL1β induces P38MAPK. The previously described HLA-DR induced by FGF2 through ERK1/2 on hBM-MSC, is suppressed by IL1β through inhibition of CIITA transcription. HLA-DR induced by IFNγ is not affected by IL1β in hBM-MSC, but is suppressed in articular chondrocytes and lung fibroblasts. Conclusions: RANKL expression and IL1β regulated MHC-class II, both induced via activation of the ERK1/2 signalling pathway, are specific for progenitor hBM-MSC expanded in the presence of FGF2. HLA-DR regulated by IL1β and ERK1/2 is observed on hBM-MSC during early expansion without FGF2 suggesting previous in vivo acquisition. Stromal progenitor cells with this phenotype could have an osteoimmunological role during bone regeneration.